The Playful Diagrams of Digital Matter: the case of The Legend of Zelda: Breath of the Wild - D’Armenio , Enzo (E|C, 2023)
This paper offers a semiotic exploration of the concepts of purport and materials in video games, structured around two primary axes. In the first part, following the concept proposed by Gilles Deleuze and revised in the light of the concept of image as environment as elaborated by Andrea Pinotti, I suggest defining interactive images as movement-images: expressive systems articulated in accordance with two interconnected groups of qualities or syntaxes: a visual and a kinetic syntax. With these concepts, an attempt is made to define the semiotic purport of the languages expressed by video games. Building upon this theoretical framework, in the second part, my paper aims to analyze the interactive dynamics of the video game The Legend of Zelda: Breath of the Wild for the way in which they build playful and creative diagrams. Elements such as water, fire, air, and electricity are digitally reproduced and engage qualities that can be manipulated by the player in relation to materials such as wood, rocks, and metals.